2012
DOI: 10.2147/idr.s27937
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival sac bacterial flora isolated prior to cataract surgery

Abstract: ObjectiveTo determine the trends of conjunctival sac bacterial flora isolated from patients prior to cataract surgery.Subjects and methodsThe study comprised 579 patients (579 eyes) who underwent cataract surgery. Specimens were collected by lightly rubbing the inferior palpebral conjunctival sac with a sterile cotton swab 2 weeks before surgery, and then cultured for isolation of bacteria and antimicrobial sensitivity testing. The bacterial isolates and percentage of drug-resistant isolates were compared amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 17 publications
6
44
3
1
Order By: Relevance
“…These conflicting results may be attributable to the differences in the DR rate between studies. The DR rates in the aforementioned studies were 86.77% for Karimsab and Razak, 12 74.8% for Arbab et al 13 and 8.29% for Suto et al 10 In our study, the rate of DR was 22.6%.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…These conflicting results may be attributable to the differences in the DR rate between studies. The DR rates in the aforementioned studies were 86.77% for Karimsab and Razak, 12 74.8% for Arbab et al 13 and 8.29% for Suto et al 10 In our study, the rate of DR was 22.6%.…”
Section: Discussionsupporting
confidence: 44%
“…Arbab et al 13 observed a positive culture rate of 75% in their PDR group compared to 20% in patients without retinopathy, and Staphylococcus epidermidis was the most common isolate. In contrast, Suto et al 10 found no difference in the frequency of positive cultures between diabetic and non-diabetic patients and no relationship between positive culture frequency and the presence of diabetic retinopathy. These conflicting results may be attributable to the differences in the DR rate between studies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…254 The bacterial isolation rate was significantly lower in dry eye patients (using only artificial tears) than for those without dry eye disease, and the use of artificial tears reduced the bacterial isolation rate compared to patients not using topical medication. Patients taking oral steroids did not have a significant difference in bacterial isolation rates.…”
Section: Dry Eye Treatment and Modulation Of Risk For Keratitismentioning
confidence: 89%